2010
DOI: 10.1080/00220381003706502
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Graduation: The Impact of EPAs on LDC Trade Space

Abstract: As trade is prominently mainstreamed into development policies, the ongoing Economic Partnership Agreement (EPA) negotiations between the EU and the African, Carribbean and Pacific (ACP) countries are a turning point in Least Developed Countries (LDC) engagement with the international trading system. The process covers most UN-designated LDCs and is the first time they feature in the first row of international trade talks. We explore how the space LDCs occupy in the trade regime will be affected by EPAs. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Existing literature on EU external relations has focused on both 'positive synergies' and 'institutional rivalry' with various international organisations (Jørgensen 2009, Jørgensen andLaatikainen 2013), particularly the WTO (Elgström and Pilegaard 2008), the United Nations (Holland 2008), the International Labour Organisation (ILO) (Orbie and Tortell 2009), and the Development Assistance Committee (DAC) (Carbone 2012). Regarding the EU's relations with the developing world, existing literature has emphasised, mostly in relation to the EPA agenda, how the EU's free trade and hard-bargaining approach has constrained the policy space of developing countries and has, in most cases, forced them to surrender policy autonomy (Storey 2006, Di Caprio and Trommer 2010, Hurt 2012.…”
Section: Policy Coherence and International Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature on EU external relations has focused on both 'positive synergies' and 'institutional rivalry' with various international organisations (Jørgensen 2009, Jørgensen andLaatikainen 2013), particularly the WTO (Elgström and Pilegaard 2008), the United Nations (Holland 2008), the International Labour Organisation (ILO) (Orbie and Tortell 2009), and the Development Assistance Committee (DAC) (Carbone 2012). Regarding the EU's relations with the developing world, existing literature has emphasised, mostly in relation to the EPA agenda, how the EU's free trade and hard-bargaining approach has constrained the policy space of developing countries and has, in most cases, forced them to surrender policy autonomy (Storey 2006, Di Caprio and Trommer 2010, Hurt 2012.…”
Section: Policy Coherence and International Developmentmentioning
confidence: 99%
“…Though we cannot disregard this contentious issue, our intention is to go beyond the EPAs, which has been the almost exclusive focus (cf. Faber and Orbie 2007) of studies that have examined the interaction between the EU's trade and development policies (Storey 2006, Elgström and Pilegaard 2008, Faber and Orbie 2009, Di Caprio and Trommer 2010, Elgström and Frenhoff-Larsen 2010, Ngangjoh-Hodu and Matambalya 2010, Hurt 2012, Langan 2012). The reason is not only that they have already been extensively researched, but also that the EPA agenda, having been outlined at the end of the 1990s, predates the above-mentioned seismic changes.…”
Section: Introductionmentioning
confidence: 98%
“…The SDT provision was designed under GATT "to acknowledge a major shortcoming of universal trade rules: the fact that they treat unequals equally" (Morgan et al 2006: 35). It was institutionalised in the 1979 Enabling Clause, which still shapes WTO negotiations today and generally serves as the basis of the developing countries' demands (Dicaprio/Trommer 2010: 1615. Under this SDT umbrella, developing countries suggested the introduction of a fourth 4 WTO box called the 'Development Box'.…”
Section: The International Agricultural Trade Regimementioning
confidence: 99%
“…While big trading nations such as the US, the EU, and China have separate, wellstaffed WTO missions in addition to their UN missions and diplomatic representations to Switzerland, the LDC missions had on average 4.1 staff members in 2008, with many of them simultaneously representing their country in all international organizations in Geneva as well as taking on consular functions (DiCaprio and Trommer, 2010). Interviewees further suggested that the quality of representation in Geneva not only depends on numbers, but also on the quality of staff.…”
Section: Transparency and Dialoguementioning
confidence: 99%